A SYMPOSIUM ON APPRECIATION. - Wildman, John R. (The Accounting Review, 1930)
Abstract The Committee on Research of the American Association of University Instructors in Accounting has assembled certain material on the subject of appreciation for review by the membership at large. Thus, an opportunity will be afforded for criticism, and for the expression of any opinion which any one may have to offer. Appreciation, because of conflicting theories and opinions held by various parties at interest, presents one of the most trying problems with which business men, lawyers and accountants have to deal. Much of the difficulty probably results from the failure to make a thorough study of the subject from all its angles. Certain graduate students at the University of Illinois, under the direction of professor A. C. Littleton, have prepared a report on a survey made by them on the subject of appreciation. This material appears in the article under the main headings and is followed in each instance by the comments of certain members of the association. In seeking a definition of appreciation, an extensive search through the accounting literature fails to yield a very rich return. The fundamental idea of an increase in values is, of course, always present.